Risk Analysis of Mulu Bebe Banana Farming in West Halmahera Regency Province North Maluku - Fatmawati Kaddas; Firlawanti Lestari Baguna; Hamidin Rasulu; Mila Fatmawati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Food production problems can contribute to global food and energy inflation; therefore, this study aims to identify the risks faced by farmers in developing Mulu Bebe banana farming, analyze the levels of production and income risks, and explore appropriate mitigation strategies. The research was conducted in West Halmahera Regency, which serves as the main production center for Mulu Bebe bananas. The study employed interviews and Focus Group Discussions (FGDs) to identify key risks experienced by local farmers. These findings were analyzed using a comprehensive risk assessment approach, including calculations of the likelihood and consequences of each risk, categorization into risk levels, grouping of risks, and prioritization of mitigation strategies, all of which were visualized through a risk map. The risks associated with Mulu Bebe banana farming were classified into two main categories: production risk and income risk. Based on the analysis, both risk types showed a coefficient of variation (CV) of less than 0.5 and a lower limit value (L) greater than 0. These indicators suggest that Mulu Bebe banana farmers generally operate under low-risk conditions and are likely to avoid significant losses in both production and income. This farming system is not entirely free from risk. Risk identification based on production and income aspects revealed several sources of risk ranging from low to high levels. The most critical risk, categorized as high, is related to technical errors in the cultivation process. Medium-level risks include pest attacks, input prices such as fertilizers and herbicides, fruit quality, seed availability, planting area, weather and climate conditions, and banana distribution infrastructure. Meanwhile, consumer preference was identified as a relatively low risk.